The fate of subducted oceanic slabs in the shallow mantle: insights from boron isotopes and light element composition of metasomatized blueschists from the Mariana forearc - Pabst, Sonja; Ludwig, Thomas (Lithos, 2011)
Serpentine muds from South Chamorro Seamount (SCS), drilled during ODP Leg 195 at Site 1200 contain metamafic clasts that experienced blueschist-facies metamorphism (including the critical mineral assemblage pumpellyite - Na-amphibole - epidote). These schists represent fragments from the actual slab-mantle interface at ~27km depth. Their heterogeneous lithology with a metasomatic character indicates significant mobility of major elements in the Mariana forearc, a region of mélange formation as it can also be observed in onland exposures such as the Catalina Schist. As the Mariana forearc blueschists show no late stage alteration they permit the direct study of material transfer during the subduction processes at an active convergent margin. This study presents the first data of detailed B isotope (δ11B) and light element variations in blueschist-facies minerals from the Mariana arc system. The primary foci are B and Li concentrations and δ11B values analyzed by SIMS and ToF-SIMS techniques. Minerals such as (Na-rich) amphibole, phengite and chlorite are found to be strongly enriched in Li (up to 70μg/g), Be (up to 8μg/g) and B (up to 35μg/g) and with δ11B values of −6±4‰. These new data are consistent with isotopically heavy B being released into the Mariana forearc mantle wedge (serpentinization of dry mantle peridotite after interaction with B-rich slab-released high pH fluids) and confirm models of significant B-loss and B isotope fractionation during forearc (shallow) slab dehydration. The elevated Li, Be and B concentrations in minerals that comprise the bulk of the rocks, namely, amphibole, phengite, and chlorite bear a strong potential to further transport Li and B as well as the isotopically light component of B to greater depths in the mantle, where ongoing metamorphism is responsible for further isotope and elemental fractionation and the formation of distinct mantle reservoirs, e.g. volcanic arc and oceanic intra-plate (OIB) magmas.